Karakterisasi Fisik dan Kimia Slag Feronikel Kecamatan Pomalaa Sulawesi Tenggara - Ichsan Invanni Baharuddin; A M Imran; Adi Maulana; Alimuddin Hamzah (Universitas Hasanuddin, 2021)
Ferronickel slag is solid waste produced from the ferronickel treatment process. This study aims to determine the physical characteristics of ferronickel slag, determine the chemical characteristics of ferronickel slag and determine the potential leaching of pollutants from the ferronickel slag in Pomalaa District. This study uses TCLP (Toxicity Characteristic Leaching Procedure) analysis to determine the leaching potential, XRD (X-Ray Diffractions) and SEM (Scanning Electron Microscope) to determine the mineral composition. Data of particle size and density of ferronickel slag were processed using Microsoft Excel. The results of XRD (X-Ray Diffractions) and SEM (Scanning Electron Microscope) analysis showed a diverse composition of ferronickel slag minerals, consisting of oxygen (O), magnesium (Mg), aluminum (Al), silica, calcium (Ca), chromium (Cr), iron (Fe), nickel (Ni), manganese (Mn) and sulfur (S). The density of ferronickel slag ranges from 3.34 g/ml - 3.53 g/ml and the particle size of ferronickel slag varies with size variations of 2 mm, 1.18 mm, 0.6 mm, 0.3 mm, 0.21 mm, 0.106 mm and 0.075 mm. TCLP analysis shows the leaching potential in nickel slag, the element boron (B) has a leaching potential of 1.10 mg/l, mercury (Hg) with a leaching potential of